2017
DOI: 10.1021/acs.orglett.7b03242
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polyfunctional Naphthyridines by Cobalt-Catalyzed Cross-Couplings of Halogenated Naphthyridines with Magnesium and Zinc Organometallics

Abstract: CoCl (5%) catalyzes cross-couplings of various halogenated naphthyridines with alkyl- and arylmagnesium halides. Also, arylzinc halides undergo smooth cross-couplings with various naphthyridines in the presence of CoCl·2LiCl (5%) and sodium formate (50%), leading to polyfunctional arylated naphthyridines. Two of these arylated naphthyridines are highly fluorescent, with quantum efficiencies reaching 95% and long excited-state lifetimes of up to 12 ns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Greiner and Knochel et al 10 reported an efficient synthesis of novel polyfunctionalized arylated naphthyridines by Co-catalyzed cross couplings between various halogenated naphthyridines and arylzinc halides, which offered the desired polyfunctional arylated naphthyridines in moderate to good yields (Scheme 6). The upsides of this protocol were that it was also suitable for the reaction of the arylmagnesium with various halogenated naphthyridines.…”
Section: Methodsmentioning
confidence: 99%
“…Greiner and Knochel et al 10 reported an efficient synthesis of novel polyfunctionalized arylated naphthyridines by Co-catalyzed cross couplings between various halogenated naphthyridines and arylzinc halides, which offered the desired polyfunctional arylated naphthyridines in moderate to good yields (Scheme 6). The upsides of this protocol were that it was also suitable for the reaction of the arylmagnesium with various halogenated naphthyridines.…”
Section: Methodsmentioning
confidence: 99%
“…All reactions involving air-or moisture-sensitive reagents were performed under a nitrogen or argon atmosphere. 1 HNMR spectra (400 MHz) and 13 CNMR (100 MHz) spectra were recorded on a Bruker BioSpin AG (Ultrashield Plus AV 400, Fällanden, Switzerland) spectrometer as deuterochloroform (CDCl 3 ) or dimethyl sulfoxide-d 6 (DMSO-d 6 ) solutions using tetramethylsilane (TMS) as an internal standard (δ = 0) unless noted otherwise. MS spectra were obtained on an Agilent technologies 6120 quadrupole LC/MS (ESI).…”
Section: General Informationmentioning
confidence: 99%
“…HPLC purity: 98.3%. 1 3-methyl-2-phenyl-8-((pyridin-3-ylmethyl)amino)-2,7-naphthyridin-1(2H)-one (10f): Yellow solid (78% yield). HPLC purity: 97.9%.…”
Section: General Procedures For the Preparation Of Targets 9a-k And 10a-smentioning
confidence: 99%
See 2 more Smart Citations